PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III.C SD NEGERI 164 PEKANBARU - Mira Astuti MZ Astuti MZ; Zariul Antosa Antosa; Zulkifli ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The problem in this research was the low student learning outcomes IPS, this happens because the learning process is only centered on the teacher so that trains students to be individual lazy thinking and has a passive nature. Besides the limited learning resources resulted in students learning to become less effective. It is necessary for research to improvements in the learning process through the implementation of cooperative learning model types think pair share. Think Pair Share (TPS) or Couples Sharing Thinking is the kind of cooperative learning are designed to affect the pattern of student interaction (Trianto, 2011). In this strategy, the child will be given a waiting time to think independently, and then discuss with a partner group. In this study, researchers gave the task in the form of worksheets. Forms of research is classroom action research (PTK). The study was conducted in two cycles, each cycle consisting of a double action learning and end of each cycle is given daily tests. Data obtained from the observation of teacher activity using observation sheet teacher activity, student activity observation using observation sheet student activity. and the daily test results of students. Test questions consisted of 20 items shaped objective, assessment refers to the assessment standards Purwanto.Hasil research shows that the average score of students is 70.02 basis increased in the first cycle to 74.80 and then increased again to 80.48 in the second cycle. So the total increase for the action amounted to 21.76%. Activity percentage of teachers in the first cycle was 67.85% increase in cycle II to 85.71%. As well as the activity of the teacher, student activities also increased. In the first cycle the percentage of student activity is 66.67%, then increased to 81.25% in the second cycle. Based on these results, it can be concluded that the implementation of cooperative learning model types think pair share can improve learning outcomes IPS graders Elementary School III.C 164 Pekanbaru Kata Kunci: Coorperative Learning Type Think Pair Share, Student Achivement the Result of IPS Studies